아키텍처 기반 소프트웨어의 일반적 요구사항과 이식성의 품질 측정 방안 - 강종업(Jong-Up Kang); 양해술(Hae-Sool Yang) (한국콘텐츠학회 논문지, 9(11), 2009)
Architecture base mechanism centers to construct software system. There is construction of successful software system how firmly define software. Reason that architecture base software is important is used and expresses early design decision item of system and is because reusability is possible by means of communication between comprehension person concerned. Analyzed special quality of pattern and importance of architecture and general requirement and portability and consider ISO/IEC 9126 and ISO/IEC 14598 and propose system and Metrik in this research. Also, do defect particulars and efficiency test that test according to examination formality of architecture base software and analyzed result. 소프트웨어 시스템을 구축하는데 아키텍처 기반 메카니즘은 중심에 있다. 성공적인 소프트웨어 시스템의 구축은 얼마나 견고하게 소프트웨어를 정의하는가에 있다. 아키텍처 기반 소프트웨어가 중요한 이유는 이해당사자 사이의 의사소통의 수단으로 사용되며 시스템의 초기 설계 결정 사항을 표현하고 재사용이 가능하기 때문이다. 본 연구에서는 아키텍처의 패턴 및 중요성 및 일반적 요구사항과 이식성의 특성을 분석하였으며 ISO/IEC 9126 및 ISO/IEC 14598을 고려하여 체계 및 메트릭을 제안하였다. 또한, 아키텍처 기반 소프트웨어의 시험절차에 따라 시험한 결함내역과 성능시험을 하고 결과를 분석하였다.